“Cuz They Straight and Everything”: Barriers to Reporting Among Gay Latino Male Sexual Assault Survivors - Daniel Jacobson López; Antonio García (American Journal of Men's Health)
There remains a paucity of research examining the barriers to reporting sexual assault among gay and bisexual male assault survivors, despite much higher sexual assault victimization rates for gay and bisexual men. Few researches have examined barriers for gay Latino and/or Black male sexual assault survivors, specifically focusing on the role of racism and homophobia. To address this gap in literature, our study examined the specific barriers to reporting sexual assault for gay Latino (including Black) male sexual assault survivors, with a focus on how their multiple marginalized identities influenced their decision-making process. The study consisted of 14 gay Latino sexual assault survivors from six cities in the United States who participated in one-on-one semistructured in-depth interviews. Our data revealed three themes: (a) Bias and Discrimination, which describes how racism, homophobia, and gendered ideology serve as barriers to reporting sexual assault; (b) the Unjust Reporting Process focuses on the unnecessarily difficult, complex, and unclear timely reporting process; and (c) Retraumatization, which describes how participants were likely to be retraumatized by reporting. Content analysis was conducted and methodology consistent with this analysis was completed. Our findings provide recommendations to enhance the reporting process for gay Latino male sexual assault survivors which include law enforcement practices (e.g., Training tailored for engaging with LGBTQIA+ individuals and male survivors) as well as agency-wide practices (e.g., trainings and groups specifically for gay and bisexual men of color). All practices should be survivor centered and trauma-informed.